Determinação social define a territorialidade da dengue no município de Uberlândia - Rodovalho, Gizele Martins (2023)
Dengue highlights some of the major urban problems: high demographic concentration, lack of basic sanitation, inadequate housing and low-quality education. Therefore, it is important to have a broad view of the relationships that occur between the transmission of Dengue and the living conditions of populations in cities, looking at social determinations by checking the surroundings, disturbances and contours in the territories. This study had the general objective of knowing the neighborhoods most affected by Dengue disease in the city of Uberlândia from 2018 to 2022. The heat maps demonstrated the path of dengue, through which we visualized in color the incidence of the disease in the neighborhoods and sectors affected, making it possible to see the recurrence of dengue disease in some neighborhoods over the years. This is a quantitative, cross-sectional, observational, descriptive, analytical, correlational study. Contains relevant elements for the analysis of health issues involving contagion with the Dengue virus in the municipality of Uberlândia, State of Minas Gerais. The population was made up of the neighborhoods that had the highest rates of Dengue in the city of Uberlândia, in the historical series from 2018 to 2022. Heat maps were also used in the Kernell model to visualize the spatialization of Dengue in the city of Uberlândia. The results could optimize the development of strategic actions to reduce Dengue cases in Uberlândia. The research was developed with approval from the Ethics and Research Committee with human beings of the Federal University of Uberlândia (CEP/UFU) following the precepts of resolution 466 of 2012 and 510 of 2016 of the National Health Council, with no. CAAE 64385822.6 .0000.5152. the vertical model that dictates what should be done to prevent Dengue, fails to disregard the territorialization of Dengue in the municipality of Uberlândia. The insistence on always using “the same model to combat Dengue” does not change the scenario, nor does it prevent or eradicate the disease. Investment should be made in actions aimed at health education, from the early years of school, mobilizing children, young people and adolescents, encouraging them to understand how important it is to carry out prevention, in order to prevent the mosquito from finding places favorable to its proliferation. Keywords Dengue. Spatialization. Health Education. Prevention. Social Determination.